Study on the tomato market in Romania in 2012-2017 - Eduard Alexandru Dumitru; Elena Daniela Şurcǎ (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
Tomatoes are an important food in the diet of Romanians. The surface, production, sales price, consumption, and the import and export of tomatoes are influenced by a number of factors analysed in this paper. Also, the tomato market, and in general the Romanian vegetable market, presents a difficult situation for which the trade balance with tomatoes shows a significant deficit (about 80 million euros in 2017) and for which a series of measures should be taken to reduce this deficit.
Keywords: Q10; Q13; Q17; 330; tomatoes; tomato produce; tomato surfaces